Psychosomatic correlations in mentally ill and mentally healthy women with infertility - A. O. Nikolaevskaya; N. A. Tyuvina; V. D. Morozova; E. P. Kesler (Неврология, нейропсихиатрия, психосоматика)
The issue of the influence of women's mental state on their reproductive function has not been adequately addressed and requires further research.Objective: a comparative evaluation of individual indicators of menstrual and reproductive function in mentally healthy and mentally ill women with infertility.Material and methods. We studied 348 women aged 21 to 40 years with primary and secondary infertility, 120 of whom had been treated for a mental disorder in a psychiatric hospital prior to the present study. The patients' condition was assessed by a clinical method using a specially designed questionnaire card.Results. Reproductive function of patients in the studied groups differed significantly in several indicators. Mentally ill women with primary infertility are characterized by the following features: later onset of menstruation, scanty or heavy menstrual flow (p<0.05), irregularity or absence of menstruation during the period of exacerbation of the disease, insufficient emotional response to menarche (p<0.05), irregularity of sexual life and dissatisfaction with it (p<0.01). Spontaneous miscarriages and stillbirth occurred more frequently in mentally ill women, especially in women with endogenous disorders (schizophrenia, affective disorders), while abortions and gynecological surgeries were more frequent in mentally healthy women (p<0.001). Predictors of infertility on the part of mental health are the early onset and chronic course of a mental disorder, the severity and duration of an exacerbation of the illness, brief and incomplete remissions, the development of personality changes or a defect (schizophrenic) as a result of a mental illness.Conclusion. Menstrual and reproductive functions of women depend on their mental state. In women with mental disorders, menstrual dysfunction together with psychopathological symptoms of illness (decrease in libido, communication, emotional numbness), decrease in social and family adaptation leads to impairment of reproductive function.